MENGUNGKAP PENGARUH RISIKO IDIOSINKRATIK: BAGAIMANA UKURAN PERUSAHAAN DAN KINERJA KEUANGAN MEMPENGARUHI HARGA SAHAM - Nining Ika Wahyuni; Mukhamad Alan Nurul Qomar; Muhammad Miqdad; Istifadah Istifadah; Markus Apriono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study explores the mediating role of idiosyncratic risk in the relationship between company size, financial performance, and stock prices in the technology sector listed on the Indonesia Stock Exchange (IDX). Secondary data were gained from the annual financial statements of technology companies conducted IPOs before 2019, excluding firms with negative equity or those under suspension, formed the basis for analysis. Path analysis using SPSS version 27 was employed to examine these relationships. The study found that company size positively and significantly have impacts on stock prices. Financial performance also shows a positive and significant influence on stock prices. Idiosyncratic risk partially mediates the relationship between company size and stock prices. Similarly, idiosyncratic risk mediates the link between financial performance and stock prices, highlighting the unique risks specific to each firm as critical factors influencing stock valuation. The study underscores the dual importance of company size and financial performance in driving stock prices while emphasizing the significant role of idiosyncratic risk in moderating these effects. These findings provide valuable insights for companies, investors, and policymakers to understand stock price fluctuations, particularly in the dynamic and high-risk technology sector. Practical implications include optimizing financial performance and managing firm-specific risks to enhance stock market performance.